Associação entre as narrativas em saúde bucal e condições socioeconômico-culturais: a dentição como reflexo da desigualdade social - Moreira, Thiago Pelúcio (2007)
This anthropological study investigates the lived-experience of oral diseases in the context of poverty in Northeast Brazil. During six months in 2004???, ethnographic interviews, narratives and participant-observation with 31 residents of the low-income community, Dendê, located in Fortaleza, Ceará were conducted and analyzed utilizing a hermeneutic-dialetic method. It is revealed that precarious life conditions make prioritizing caretaking a difficult task. Despite suffering tooth pain, seeking a dentist's care is perceived as "a luxury" not a citzens' right. Difficulties in accessing services and poor quality restorations, favor tooth extractions as the most effective intervention. The deterioration of one's oral health is lamented by community members who seek help from popular clinics, politicians and traditional healers. The experience of dental disease differs according to social class, leaves oral scars of inequity, harms self-esteem and inhibits social inclusion. In this context, "treating" the Teeth of Inequity demands that we deepen our comprehension of the social determinants of health, reduce injustice in the access to quality care, remove demoralizing stigmas and empower the community to confront structural forces which affect its life